Quadrilateral Patterns for Rigid Folding Structures. (March 2014) - Stavric, Milena; Wiltsche, Albert
In this paper we will do investigations on spatial quadrilateral meshes developed from folding patterns. The simplicity of manual production in combination with the geometrical complexity of paper folding shall lead to an inspiration for designing architectural structures. We propose geometrical methods for designing these quadrilateral structures which follow in their shape geometrical surfaces. Our methods use folding patterns where only four folding lines meet in one node and every quadrangular part stays flat. This enables simpler solutions for architectural realization in a big scale especially for join connections and assembling of the whole spatial and structural system. In order to understand and handle the complexity of paper folding we use CAD tools to model the structures where the entire folding element is reconstructed and its geometric characteristics are controlled. This kind of control reflects on scale models. Models are then adjusted, examined and built to reach certain further geometric conclusions that are once more tested in CAD software.